Digital Communication Dynamics in Game Character Communities: A Study on r/furinamains on Reddit - Fikry Zahria Emeraldien; Nur Azizi Juliansyah; Tosti Hsucheng Chiang (Universitas Tribhuwana Tungga Dewi, 2025)
This research studies the dynamics of digital interaction within the Genshin Impact fan community on the subreddit r/furinamains. As part of the broader Genshin Impact fandom, this group utilizes the online platform as an open and collaborative space for social engagement. Use netnographic methods, we analyze how members construct shared identities, foster solidarity, and engage in symbolic self-expression through everyday interactions. Data were collected over a three-month period (January–March 2024) through passive observation and documentation of approximately 150 posts and comment threads within the subreddit. Thematic analysis was employed to identify communication patterns, symbolic forms, and participation dynamics among members. Findings reveal that communication occurs across multiple languages and is shaped by Reddit features such as tagging, upvoting, and moderation. Dominant discursive forms include setting discussions, speculative theories, inside jokes, and sarcastic comments, all contributing to social cohesion and collective identity formation. Symbolic practices were particularly evident in the use of memes, character nicknames, fan art, and specially created visual content, functioning as tools for symbolic interaction. These practices were reinforced both by the platform's mechanisms and by moderators' efforts to maintain norms and regulate conversation. This study demonstrates that communities like r/furinamains are not merely casual gathering places, but spaces where symbolic products are created, digital identities are formed, and participation in everyday life within the social media era occurs. This research contributes to a deeper understanding of how digital communications support vibrant virtual communities rooted in shared fandom and interests. Penelitian ini mengkaji dinamika komunikasi digital dalam komunitas penggemar karakter Furina di subreddit r/furinamains. Sebagai bagian dari ekosistem fandom global Genshin Impact, komunitas ini memanfaatkan platform digital sebagai ruang interaksi sosial yang inklusif dan kolaboratif. Dengan menggunakan pendekatan netnografi, penelitian ini menelusuri bagaimana anggota komunitas membangun identitas kolektif, solidaritas, serta ekspresi simbolik melalui interaksi daring. Data penelitian dikumpulkan selama tiga bulan, dari Januari hingga Maret 2024, melalui observasi pasif dan dokumentasi sekitar 150 unggahan serta rangkaian komentar di subreddit tersebut. Analisis dilakukan dengan pendekatan tematik untuk mengidentifikasi pola komunikasi, bentuk simbolik, serta dinamika partisipasi anggota komunitas. Hasil penelitian menunjukkan bahwa pola komunikasi berlangsung secara satu arah, dua arah, maupun multi-arah, yang dimediasi oleh fitur Reddit seperti komentar bertingkat, sistem voting, dan moderasi komunitas. Tema dominan dalam diskusi meliputi lore, teori spekulatif, humor internal, dan sarkasme, yang secara bersama-sama membentuk kohesi sosial dan menciptakan makna kolektif. Simbol-simbol digital seperti meme, fanart, julukan karakter, dan istilah khusus menjadi elemen kunci dalam proses interaksi simbolik. Selain itu, peran platform dan moderator juga terbukti penting dalam menjaga norma komunitas serta mengarahkan diskusi. Hasil penelitian menegaskan bahwa komunitas daring seperti r/furinamains bukan sekadar ruang hiburan, tetapi merupakan arena produksi simbolik, pembentukan identitas digital, dan partisipasi budaya di era media sosial. Studi ini berkontribusi pada pemahaman mengenai peran komunikasi digital dalam membentuk komunitas virtual berbasis minat dan fandom yang berkembang secara dinamis.